Effects of Organic Load on Basic Geotechnical Properties of Compacted Sand-kaolinite Mixture - Abd. Rahman, Rakmi; M. A., Mannan (Universiti Putra Malaysia Press, 1995)
In the laboratory, four PVC sand-kaolinite mixture columns, each of 150 cm depth and 15 cm diameter, were fed with solutions of sodium acetate equivalent to 20,000 p.p.m., 30,000 p.p.m., 40,000 p.p.m., and 50,000 p.p.m. BOD (biochemical oxygen demand). Soil physical and chemical properties, such as Atterberg limits, specific gravity, soil pH and soil organic content, altered markedly within 40 days of continuous feeding. The results showed that feed with higher BOD values increased the soil organic content as well as soil pH; and thereby the specific gravity and Atterberg limits were lowered.